Pharmacokinetic drug evaluation of ezetimibe + simvastatin for the treatment of hypercholesterolemia. (3rd October 2017) - Bove, Marilisa; Fogacci, Federica; Cicero, Arrigo F. G.
ABSTRACT: Introduction : Cholesterol lowering treatment is mainly based on statins eventually associated to adjunctive drugs of different class such as ezetimibe. In the present review, we analysed the pharmacokinetics, efficacy and safety of ezetimibe + simvastatin drug association. Areas covered : The bio-equivalence of ezetimibe and simvastatin when co-administrated in separate tablets or combined in a single pill is well documented. Ezetimibe is absorbed in small intestine, reaching peak plasma concentrations in 4–12 h, with a plasma half-life of 22 h. Simvastatin, ingested as a prodrug, is hydrolyzed in liver to its active beta-hydroxyacid metabolite, reaching peak plasma concentrations in 2–4 h, with a plasma half-life of approximately 5 h. The available evidence support the clinical efficacy of this drug combination, both in term of LDL-cholesterol reduction and cardiovascular risk decrease. Expert opinion : The synergistic action of these two drugs and the efficacy and safety extensively demonstrated of their association (in particular in the large IMProved Reduction of Outcomes: Vytorin Efficacy International Trial -IMPROVE-IT-) promote its clinical use, especially in subjects with high cardiovascular risk who need to optimize their LDL-Cholesterolemia, but also in patients who cannot tolerate high-dose of more powerful statins.